2017
DOI: 10.1213/ane.0000000000001854
|View full text |Cite
|
Sign up to set email alerts
|

Why Anesthesiologists Must Incorporate Focused Cardiac Ultrasound Into Daily Practice

Abstract: The size, availability, cost, and quality of modern ultrasound devices have, for the first time in modern medicine, enabled point-of-care ultrasound by the noncardiologist physician. The appropriate application of focused cardiac ultrasound (FoCUS) by anesthesiologists has the potential to alter management and affect outcomes for a wide range of patients. In this article, the indications, benefits, and limitations of FoCUS are described. The training and equipment required to perform FoCUS are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 27 publications
0
23
0
4
Order By: Relevance
“…A MEDLINE search for the terms ''POCUS'', ''point-of-careultrasound'', or ''bedside ultrasound'' showed that only 60 articles were published in 1990 compared with 1,030 in 2016. To facilitate the implementation of POCUS into anesthesia care, there has been strong advocacy for its integration into residency and postgraduate training, 5,38,46,65,[67][68][69][70][71][72] with convincing evidence that POCUS is a skill that can be readily acquired at all levels of training. 5,11,46,47,69,73 Despite the numerous applications, great potential for patient care, and recent growth in the use of POCUS in anesthesia, there are still barriers that prevent it from being a current standard practice and challenges in establishing anesthesia-specific guidelines.…”
Section: Résumémentioning
confidence: 99%
“…A MEDLINE search for the terms ''POCUS'', ''point-of-careultrasound'', or ''bedside ultrasound'' showed that only 60 articles were published in 1990 compared with 1,030 in 2016. To facilitate the implementation of POCUS into anesthesia care, there has been strong advocacy for its integration into residency and postgraduate training, 5,38,46,65,[67][68][69][70][71][72] with convincing evidence that POCUS is a skill that can be readily acquired at all levels of training. 5,11,46,47,69,73 Despite the numerous applications, great potential for patient care, and recent growth in the use of POCUS in anesthesia, there are still barriers that prevent it from being a current standard practice and challenges in establishing anesthesia-specific guidelines.…”
Section: Résumémentioning
confidence: 99%
“…[4] A comprehensive TTE examination involves the use of specific equipment, assists with diagnosing pathology, and requires a larger knowledge base with specialised training. FOCUS as a screening modality has a more focused scope, and is used to answer a specific clinical question, often looking for a 'yes' or 'no' answer.…”
Section: Cmementioning
confidence: 99%
“…This application does not require cardiology knowledge, and less intensive training is needed. [4] However, interpretation of the images requires adequate training and is operator dependent. Clinical common sense is also needed to apply the additional echo findings to the clinical scenario.…”
Section: Cmementioning
confidence: 99%
“…3 In addition, a recent editorial presented evidence in support of the daily use of FoCUS by anesthesiologists, further promoting its potential as the "21stcentury stethoscope." 12,13 In this review, we discuss the role FoCUS has for regional anesthesiologists and pain specialists. We will introduce the regionalist to the normal sonoanatomy of the basic FoCUS views and then use the Indication, Acquisition, Interpretation, and Medical decision making (I-AIM) framework to present the cardiac pathology most relevant to the regional anesthesiologist and pain specialist in the perioperative setting.…”
mentioning
confidence: 99%